Using Social Media to Improve Female Students’ Knowledge of School Health Programs (UKS) for Addressing Adolescent Nutritional Problems - Azrimaidaliza, Azrimaidaliza; Usman, Hendrizal; Apriliani, Annisa Dwi; Risya, Annisa Nurfitri; Muthmainah, Afiyah; Apriola, Annisa; Susanti, Esi (Warta Pengabdian Andalas, 2025)
The adolescent age group is particularly vulnerable to nutrition problems, mainly female adolescent. Therefore, every school, especially Junior High School (SMP), should have a School Health Program (UKS) to enhance healthy living skills and prevent and address nutrition and health issues among adolescents. The program includes extracurricular activities, blood supplement tablets, nutritional status checks, Clean and Healthy Lifestyle Behavior (PHBS) programs, and other health activities. The aim of the activities is to increase students' knowledge about the role of UKS in addressing adolescent nutrition and health issues. The activity was conducted for 10 students from SMP Negeri 21 Padang on Saturday, June 8, 2024. The method involved educational provision using poster and electronic pocketbook media delivered online through a WhatsApp group. The materials covered the definition and objectives of UKS, nutrition and health problems among adolescents, and the role of UKS in addressing these issues. Pre-post test was conducted to examine knowledge improvement after giving nutrition education and was analysed using dependent t-test. The result of this activity showed the positive impact of nutrition education on increasing students' knowledge (mean score pre-post test=52.0 vs 70.0; p-value=0.004). With this increased knowledge, it is hoped that increased the role of female students and being actively involved in UKS activities to overcome nutritional problems among adolescents.